Software Design of Mobile Antenna for Auto Satellite Tracking Using Modem Correction and Elevation Azimuth Method - Sirat, Djamhari; Asvial, Muhamad; Diponegoro, Arman Djohan; Sidharta, Himawan (Makara Journal of Technology, 2010)
Software Design of Mobile Antenna for Auto Satellite Tracking Using Modem Correction and Elevation Azimuth Method. Pointing accuracy is important in satellite communication. Because the satellite’s distance to the surface of the earth's satellite is so huge, 1 degree of pointing error will make the antenna unable to send data to satellites. To overcome this, the auto-tracking satellite controller is made. This system uses a microcontroller as the controller, with the GPS as the location indicator of the antenna, a digital compass as the beginning of antenna pointing direction, a rotary encoder as azimuth and elevation censor, and a modem to see Eb/No signal. The microcontroller uses serial communication to read the input. Thus, the programming should be focused on the Universal Asynchronous Receiver/Transmitter (UART) and serial communication software UART. This controller has 2 phases in the process of tracking satellites. The early stage is the elevation-azimuth method, in which with input from the GPS and digital compass, the position of satellites (both coordinates and height) is stored in the microcontroller. The controller will measure the elevation and azimuth angle, then it will move the antenna according to the antenna azimuth and elevation angle. The next stage is correction modem, in which the controller only uses the modem as the input, and antenna movement is set up to obtain the largest value of Eb/No signal. The results of the controller operation show that there is a change in the value of the original input level from -81.7 dB to -30.2 dB with end of Eb/No value reaching 5.7 dB.